2000
DOI: 10.1016/s0014-5793(00)02317-6
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma extract activates MAP kinases and induces the neuronal differentiation of rat pheochromocytoma PC12 cells

Abstract: The pharmacology and clinical application of traditional Chinese medicine has been extensively documented. We have used an in vitro model system, PC12 cells, to demonstrate the presence of neuroactive compounds in Ganoderma lucidum (lingzhi). Ganoderma extract induced the neuronal differentiation of PC12 cells and prevented nerve growth factor-dependent PC12 neurons from apoptosis. Moreover, these effects of ganoderma might be mediated via the ras/extracellular signalregulated kinase (Erk) and cAMP-response el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 21 publications
3
83
0
Order By: Relevance
“…In addition, G. lucidum extract was shown to activate MAPKs and mediate the neuronal differentiation and neuroprotection of rat pheochromocytoma PC12 cells (20), perhaps via the Ras/ERK and CREB signal transduction pathways (20). The real carbohydrate epitope responsible for the antitumor activity and its receptor have not been identified, however, although the complement receptor type 3 (CR3) has been shown to bind ␤-glucan PS with undefined side chains (see Ref.…”
mentioning
confidence: 99%
“…In addition, G. lucidum extract was shown to activate MAPKs and mediate the neuronal differentiation and neuroprotection of rat pheochromocytoma PC12 cells (20), perhaps via the Ras/ERK and CREB signal transduction pathways (20). The real carbohydrate epitope responsible for the antitumor activity and its receptor have not been identified, however, although the complement receptor type 3 (CR3) has been shown to bind ␤-glucan PS with undefined side chains (see Ref.…”
mentioning
confidence: 99%
“…The fruiting bodies and cultured mycelia of Ganoderma lucidum have been demonstrated to possess anti-tumor activities, 10 -18 immunomodulatory activities, 19 -20 and neuroactive effects. 21 Although numerous studies on the effects of water extracts of GL have been reported, 10 -16 little is known regarding its alcohol extracts. It has been reported that the alcohol extract of Ganoderma lucidum can induce cell cycle arrest at transition from G1 to S phase in HeLa-cells 17 This study was designed to further investigate the anti-tumor effects of alcohol extracts of Ganoderma lucidum and elucidate the potential mechanisms using an in vitro system.…”
mentioning
confidence: 99%
“…Reference plasmid pCMV␤gal was co-transfected to serve as internal control for normalizing the transfection efficiency. MTT assays and ␤-galactosidase assays were performed as previously described (Roche Molecular Biochemicals) (22). BrdUrd incorporation assays were performed using BrdUrd-based cell proliferation enzyme-linked immunosorbent assay (Roche Molecular Biochemicals).…”
Section: Methodsmentioning
confidence: 99%